Female Entrepreneurship and the Metanarrative of Economic Growth: A Critical Review of Underlying Assumptions. (26th December 2017) - Dean, Hannah; Larsen, Gretchen; Ford, Jackie; Akram, Muhammad
Abstract: This critical review of the literature on female entrepreneurship problematizes the metanarrative of economic growth and the mechanisms through which it both operates and is maintained. Central to this is the axiomatic 'underperformance hypothesis', which states that 'all else being equal, female entrepreneurs tend to be less successful than their male counterparts in terms of conventional economic performance measures' (Du Rietz and Henrekson (2000, p. 1). As an axiom, the truth of the 'underperformance hypothesis' is taken for granted, and thus it invisibly serves as a starting point, delimiter and interpretive lens for analysis in this field. While it remains invisible, the hypothesis will continue to reproduce the differences between male and female entrepreneurs, and thus the subordination of women to men in the realm of entrepreneurship. The review illustrates how, by associating females with underperformance, the persistent influence of the metanarrative of economic growth has been masked and the image of the female entrepreneur as problematic and inferior to her male counterpart has been reinforced. The authors argue that a postmodern feminist epistemology will destabilize both the metanarrative of economic growth, and the axiomatic 'underperformance hypothesis' it supports, thus opening up space for a heterogeneous understanding of (female) entrepreneurship. By questioning accepted knowledge about female entrepreneurs, the review sets the platform for the exploration of new research questions and a broad agenda for future research. Such an agenda is crucial in order to move future research beyond the pervasive influence of the metanarrative of economic growth and its attendant underperformance hypothesis.